STRATEGI GURU KELAS DALAM MENGATASI PESERTA DIDIK YANG MENGALAMI KESULITAN MEMBACA DI KELAS 1 SDN 10 LANGKAI DITINJAU DARI METODE MULTISENSORI - Aulia Yasmin Indi Hanifah; Diplan; Abd Rahman Azahari; Kristiani Natalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the difficulties in early reading experienced by first-grade students at SDN 10 Langkai, such as recognizing letters, distinguishing letter sounds, and combining letters into simple words. To address these issues, teachers implemented a multisensory learning method involving visual, auditory, kinesthetic, and tactile aspects. This study aims to describe the teacher’s strategies in overcoming reading difficulties and to identify the outcomes of the multisensory method applied to students. This research employed a descriptive qualitative approach, with research subjects consisting of first-grade teachers, students experiencing reading difficulties, and their parents. Data were collected through observation, semi-structured interviews, and documentation. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The results indicate that the implementation of the multisensory method was carried out effectively and had a positive impact on students’ reading abilities. The visual aspect was applied through the use of pictures and letter cards, the auditory aspect through repetition of letter sounds, the kinesthetic aspect through movement activities, and the tactile aspect through the use of concrete media. This approach improved students’ ability to recognize letters, pronounce sounds accurately, and read simple words. In addition, students became more active, enthusiastic, and confident in the learning process. However, the improvement was not evenly distributed among students, as it was influenced by differences in initial ability, learning motivation, and parental support. Therefore, consistent implementation at school and support from families are needed to optimize students’ reading development.